Effects of exercise dose based on the ACSM recommendations on patients with post-stroke cognitive impairment: a systematic review and meta-analyses - Zhao, Xuejiao; Li, Juan; Xue, Chao; Li, Yujie; Lu, Ting (Frontiers in Physiology, 2024)
Purpose: This review aimed to assess the impact of different exercise dosages on cognitive function in individuals with post-stroke cognitive impairment (PSCI).Methods: Four electronic databases-Embase, PubMed, Web of Science, and Cochrane Librarywere systematically searched from inception to January 01, 2024, focusing on the impact of exercise therapy on cognitive function in individuals with PSCI. Only randomized controlled trials meeting the criteria were included. The exercise therapy dose and adherence were evaluated following the American College of Sports Medicine (ACSM) guidelines, categorized into a high compliance group with ACSM recommendations and a low or uncertain compliance group. A random-effects model compared the effect of ACSM compliance on cognitive function in individuals with PSCI, with the effect size represented by the standardized mean difference (SMD) and a 95% confidence interval (CI).Results: In total, 18 studies meeting the criteria were included, with data from 1,742 participants. The findings suggested a beneficial effect of exercise on cognitive function in individuals with PSCI [SMD = 0.42, 95% CI (0.20, 0.65)]. Ten studies were categorized as the "high adherence group" and eight in the "low or uncertain adherence group" based on the ACSM recommendations. The subgroup analysis revealed that the SMD of the high compliance group was 0.46 (95% CI: 0.10, 0.82) (P = 0.01), while the SMD of the low or uncertain compliance group was 0.38 (95% CI: 0.07, 0.70) (P = 0.02).Our study indicates the beneficial impact of exercise for patients with PSCI over no exercise. Furthermore, high adherence to the exercise dose recommended by ACSM guidelines demonstrated a more substantial improvement in cognitive function than low or uncertain adherence in patients with PSCI.